TELEMEDICINE AS A SOCIO-TECHNICAL INNOVATION IN CONTEMPORARY HEALTHCARE SYSTEMS: APPLICATIONS, BENEFITS, CHALLENGES AND FUTURE PERSPECTIVES - Joanna Gontarczyk; Paulina Makowska; Alicja Laske; Natalia Sitko; Martyna Sowa; Antoni Majda; Julia Pająk; Kacper Kucharski; Anna Kamosińska; Adam Kowal; Julia Sokołowska; Marcel Dawidowicz (International Journal of Innovative Technologies in Social Science, 2026)
Telemedicine has emerged as a transformative innovation in contemporary healthcare systems, with its rapid expansion significantly accelerated during the COVID-19 pandemic. This study aims to analyze the effectiveness, economic impact, and patient satisfaction associated with telemedicine, as well as to identify key barriers to its implementation and future development directions.A narrative literature review was conducted based on systematic reviews, meta-analyses, and empirical studies published between 2008 and 2026, covering applications in primary care, chronic disease management, mental health services, and remote patient monitoring.The findings indicate that telemedicine provides outcomes comparable to traditional in-person care in many clinical settings, particularly in chronic disease management, where it contributes to improved health outcomes and reduced hospitalizations. Additionally, telemedicine demonstrates significant cost-saving potential and consistently high levels of patient satisfaction due to improved accessibility and convenience.However, several challenges remain, including technological limitations, regulatory constraints, and disparities in digital access, which may hinder large-scale and equitable implementation.The study concludes that telemedicine represents a key direction in the development of innovative healthcare systems, but its long-term success depends on addressing systemic barriers and integrating digital solutions into hybrid models of care.